Multifunctional fluorine‐free superhydrophobic coating with flame‐retardant, anti‐icing, anti‐corrosion, and oil–water separation properties. Issue 1 (17th February 2022) - Li, Shuyi; Xie, Chuankun; Zhang, Wenliang; Wei, Dongsong; Zheng, Zaihang; Liu, Yan
Abstract: A fluorine‐free and multifunctional superhydrophobic coating (r‐MSC) was prepared by the one‐step spraying method. The coating had superhydrophobic and low‐adhesion properties with the water contact angle of 161.5° ± 1° and the sliding angle of 3.2° ± 0.5°. It could be prepared by spraying while maintaining superhydrophobic surface characteristics on any substrates. The coating owed outstanding mechanical durability and chemical stability. Moreover, the coating also possessed the ability of self‐cleaning, anti‐fouling, anti‐icing, and flame retardant ability. Importantly, the presence of multifunctional coating endowed the substrate with both water‐resistant and fireproof properties. Besides, it also showed excellent oil‐water separation ability, which presented the oil‐water separation efficiency of over 90% for different types of oils after 10 separation cycles. Furthermore, the coating could improve corrosion inhibition performance and the corrosion current density was reduced by two orders of magnitude from the polarization curve. The r‐MSC had the advantages of simple preparation, fluorine‐free, environmentally friendly and appropriate for large‐area fabrication, which could be applied to various fields.